Coast to coast hockey in Canada to the Second World War (Univ. of Toronto Press, 2009)
"In Coast to Coast, a wide range of contributors examine the historical development of hockey across Canada, in both rural and urban settings, to ask how ideas about hockey have changed. Conceptually broad, the essays explore identity formation by investigating what hockey meant to Canadians from the nineteenth century to the Second World War, as well as the role of government, entrepreneurs, and voluntary associations in supporting and promoting the game."--BOOK JACKET.